2020
DOI: 10.1016/j.neuropharm.2019.107856
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and biotransformation studies of 1-acyl-substituted derivatives of -lysergic acid diethylamide (LSD)

Abstract: The ergoline d-lysergic acid diethylamide (LSD) is one of the most potent psychedelic drugs. 1-Acetyl-LSD (ALD-52), a derivative of LSD containing an acetyl group on the indole nitrogen, also produces psychedelic effects in humans and has about the same potency as LSD. Recently, several other 1-acyl-substitued LSD derivatives, including 1-propanoyl-LSD (1P-LSD) and 1butanoyl-LSD (1B-LSD), have appeared as designer drugs. Although these compounds are assumed to act as prodrugs for LSD, studies have not specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 78 publications
(102 reference statements)
5
45
0
Order By: Relevance
“…ALD‐52, 1P‐LSD, and 1B‐LSD have been shown to elicit the HTR and it appears that this is the result of LSD formation in vivo 18,24 . Compared with LSD, ALD‐52, 1P‐LSD, and 1B‐LSD bind to the 5‐HT 2A receptor with lower affinity and act as very weak 5‐HT 2A partial agonists in a Ca 2+ flux assay 24 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…ALD‐52, 1P‐LSD, and 1B‐LSD have been shown to elicit the HTR and it appears that this is the result of LSD formation in vivo 18,24 . Compared with LSD, ALD‐52, 1P‐LSD, and 1B‐LSD bind to the 5‐HT 2A receptor with lower affinity and act as very weak 5‐HT 2A partial agonists in a Ca 2+ flux assay 24 …”
Section: Introductionmentioning
confidence: 99%
“…It was shown recently that 1‐acylated lysergamides likely serve as prodrugs to either LSD (1P‐LSD, 1B‐LSD, ALD‐52) 18,19,22–24 or N 6 ‐ethyl‐nor‐LSD (ETH‐LAD) (from 1P‐ETH‐LAD), 19,22 suggesting that the detection of the parent 1‐acylated lysergamide in vivo following ingestion might be challenging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations have also shown that the affinity of ALD‐52, 1P‐LSD, and 1B‐LSD to most monoamine receptors dropped by one to two orders of magnitude compared to LSD and that they showed a weak efficacy or even acted as antagonists in Ca 2+ ‐ mobilization assays. The fact that these substances however were able to induce the head‐twitch response in mice and that LSD was detected in rat plasma samples was also consistent with the idea that 1‐acyl‐substituted LSD derivatives might serve as prodrugs .…”
Section: Prodrugs Of Psychoactive Substancesmentioning
confidence: 99%